Perkembangan terapi insulin konvensional hingga insulin analog: Literatur review - Khoirunnisa, Hasna; Kamilah, Putri; Adiyatma, Raditya; Syifa, Salma Nabila; Mufidah, Salwa; Nada, Zakiyyah Qothrun; Ridwan, Heri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The increasing prevalence of diabetes mellitus (DM) globally demands the development of more effective and physiological insulin therapies. Although DNA-engineered conventional human insulin has replaced animal insulin since the 1980s, conventional insulin has drawbacks, such as a pharmacokinetic profile that does not match human physiology, slow absorption, and a higher risk of nocturnal hypoglycemia. Purpose: To comprehensively assess advances in insulin therapy, highlighting key differences in pharmacokinetics, clinical efficacy, and safety between conventional and analog formulations. Method: This study employed a literature review design with a literature search of PubMed, Google Scholar, and OpenAlex databases using the keywords: "Diabetes Mellitus," "Insulin," "Insulin Analog," and "Conventional Insulin." Results: Analog insulins have a more consistent pharmacokinetic profile (such as rapid onset of action and stable duration in long-acting analogs) and potentially reduce the risk of hypoglycemia, thus improving glucose control. However, several local studies have shown that the effectiveness of analog insulins and conventional human insulin in reducing HbA1c levels and the incidence of hypoglycemia is not significantly different. Conclusion: Recent developments such as inhaled insulin, smart insulin, and artificial pancreas (closed-loop) systems offer opportunities for more personalized therapy, although cost and accessibility remain challenges.   Keywords: Analog Insulin; Conventional Insulin; Diabetes Mellitus; Insulin.                                          Pendahuluan: Meningkatnya prevalensi diabetes mellitus (DM) secara global menuntut pengembangan terapi insulin yang lebih efektif dan fisiologis. Meskipun insulin konvensional manusia yang direkayasa DNA telah menggantikan insulin hewan sejak tahun 1980-an, insulin konvensional memiliki kekurangan, seperti profil farmakokinetik yang tidak sesuai dengan fisiologi tubuh, penyerapan lambat, dan risiko hipoglikemia nokturnal yang lebih tinggi. Tujuan: Untuk menilai secara komprehensif kemajuan dalam terapi insulin, dengan menekankan perbedaan penting dalam aspek farmakokinetik, kemanjuran klinis, dan keamanan antara formulasi konvensional dan analog. Metode: Penelitian ini menggunakan desain tinjauan literatur dengan pencarian literatur dari basis data PubMed, Google Scholar, dan OpenAlex menggunakan kata kunci: "Diabetes Mellitus", "Insulin", "Insulin Analog", dan "Insulin Konvensional". Hasil: Insulin analog memiliki profil farmakokinetik yang lebih konsisten (seperti onset aksi yang cepat dan durasi yang stabil dalam analog yang bekerja lama) dan berpotensi mengurangi risiko hipoglikemia sehingga meningkatkan kontrol glukosa. Namun, beberapa studi lokal menunjukkan bahwa efektivitas insulin analog dan insulin manusia konvensional dalam menurunkan kadar HbA1c dan kejadian hipoglikemia tidak berbeda secara signifikan. Simpulan: Perkembangan terbaru seperti insulin inhalasi, insulin pintar, dan sistem artificial pancreas (closed-loop) menawarkan peluang untuk terapi yang lebih personal, meskipun kendala biaya dan aksesibilitas tetap menjadi tantangan.   Kata Kunci: Diabetes Mellitus; Insulin; Insulin Analog; Insulin Konvensional.